2007
DOI: 10.1073/pnas.0709955104
|View full text |Cite|
|
Sign up to set email alerts
|

A mathematical tool for exploring the dynamics of biological networks

Abstract: We have developed a mathematical approach to the study of dynamical biological networks, based on combining large-scale numerical simulation with nonlinear “dimensionality reduction” methods. Our work was motivated by an interest in the complex organization of the signaling cascade centered on the neuronal phosphoprotein DARPP-32 ( d opamine- and c A MP- r egulated p hospho p rotein of molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 27 publications
(23 reference statements)
2
32
0
Order By: Relevance
“…The resulting models can be very high dimensional in both states and parameters and a central concern in the field is how such complex models can be used when many of the parameter values are unknown. There are many perspectives on this problem: some properties of systems can be proved to be independent of parameter values (Feinberg 1995;Angeli et al 2004); parameters can be estimated from data in statistically meaningful ways ( Jaqaman & Danuser 2006); methods of dimensionality reduction can reduce complexity (Barbano et al 2007); some properties of systems have been found empirically to be robust to parameter variation (Alon et al 1999;von Dassow et al 2000); and both theory and empirical results suggest that, for any given phenotypic behaviour, only an exponentially small number of parameters are significant (Rand et al 2005;Gutenkunst et al 2007). We note further that both pharmaceutical and biotechnology companies are adopting modelling in drug development (Bangs & Paterson 2003;Hendriks et al 2006;Haberichter et al 2007), suggesting that model complexity is not a barrier to usefulness.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting models can be very high dimensional in both states and parameters and a central concern in the field is how such complex models can be used when many of the parameter values are unknown. There are many perspectives on this problem: some properties of systems can be proved to be independent of parameter values (Feinberg 1995;Angeli et al 2004); parameters can be estimated from data in statistically meaningful ways ( Jaqaman & Danuser 2006); methods of dimensionality reduction can reduce complexity (Barbano et al 2007); some properties of systems have been found empirically to be robust to parameter variation (Alon et al 1999;von Dassow et al 2000); and both theory and empirical results suggest that, for any given phenotypic behaviour, only an exponentially small number of parameters are significant (Rand et al 2005;Gutenkunst et al 2007). We note further that both pharmaceutical and biotechnology companies are adopting modelling in drug development (Bangs & Paterson 2003;Hendriks et al 2006;Haberichter et al 2007), suggesting that model complexity is not a barrier to usefulness.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is often referred to as "robustness", and simulation has begun to play a role in elucidating its molecular basis. Based on combining large-scale numerical simulation with nonlinear "dimensionality reduction" methods, Paolo et al [35] developed a mathematical approach to the study of dynamical biological networks, to detect robust features of the system in the presence of noise. Firstly, the data was reduced with their dimension using locally linear embedding (LLE) and Laplacian eigenmaps (LEs) method to simplify the complexity of subsequent data processing.…”
Section: Differential Equation Modelmentioning
confidence: 99%
“…A number of models of dopamine (DA) and Ca 2+ signal integration have included only Thr34 and Thr75 as major switching factors between LTP and LTD [17,18,29,105]. A few models incorporate all four phosphorylation sites [19,106].…”
Section: Biophysical Models Of Synaptic Plasticitymentioning
confidence: 99%